2018
DOI: 10.1016/j.heliyon.2018.e01070
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the efficacy of a Salmonella Enteritidis live vaccine for chickens according to the current European Pharmacopoeia Monograph

Abstract: Since 2013 the efficacy of new live Salmonella Enteritidis (SE) vaccines for chickens needs to be demonstrated according to European Pharmacopoeia Monograph 04/2013:2520 to receive approval in the EU. The purpose of this study was to determine whether a vaccine licensed since 1999 could also fulfil the required tests of the current guideline. For this, Salmonella-free chickens (n = 50) were vaccinated on their 2nd, 46th and 84th day of life with the live attenuated S. Enteritidis strain IDT No. 441/014. Non-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…However, they could not show a significantly reduced excretion of the challenge strains, measured by the number of Salmonella positive cloacal swabs, independently from the different vaccination regimen. This contrasts with the results of Theuß et al [10], showing a significant and relevant reduction of the number of positive cloacal swabs after threefold vaccination with a SE-LV.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, they could not show a significantly reduced excretion of the challenge strains, measured by the number of Salmonella positive cloacal swabs, independently from the different vaccination regimen. This contrasts with the results of Theuß et al [10], showing a significant and relevant reduction of the number of positive cloacal swabs after threefold vaccination with a SE-LV.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus it can be assumed that the Salmonella group D specific antibodies detected are antibodies against S. Enteritidis. The increase of the specific antibody titers after vaccination with the SE-LV and subsequent challenge with virulent S. Enteritidis strains corresponds to reports from Methner [7], Springer et al [9] and Theuß et al [10]. The increase after vaccination is usually much lower than after infection.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Long persistence in tissues was conceived to induce protective immune responses by live attenuated vaccines. The negative results for Salmonella revealed that these vaccine strains could not colonize and invade livers, spleen, ovaries, and oviducts, which the wild type of Salmonella most frequently targeted ( Theuß et al., 2018 ). The stimuli of vaccine stains may have been sufficient for well-established adaptive immunity before the time of visceral sample collections (week 25).…”
Section: Discussionmentioning
confidence: 99%